Developing sponsorship marketing : Finnish perspective - Korkka, Ville (2010)
This thesis deals with sponsorship marketing development in sport in Finnish marketplace and aims to study how sponsoring companies perceive the current situation of the sponsorship marketing, and the main issues sponsored targets should take into account in their product development to meet sponsors’ demands in the future. This thesis also examines how current sponsors perceive current sponsorship marketing relations with Blues Hockey, the employer of this research. Furthermore, this thesis clarifies the main issues Blues Hockey should take into account to develop its product portfolio to meet sponsors’ demands in the future.